2018
DOI: 10.1038/s41598-018-25358-z
|View full text |Cite
|
Sign up to set email alerts
|

mTOR complexes differentially orchestrates eosinophil development in allergy

Abstract: Eosinophil infiltration is considered a hallmark in allergic airway inflammation, and the blockade of eosinophil differentiation may be an effective approach for treating eosinophil-related disorders. Mammalian target of rapamycin (mTOR) is a vital modulator in cell growth control and related diseases, and we have recently demonstrated that rapamycin can suppress eosinophil differentiation in allergic airway inflammation. Considering its critical role in haematopoiesis, we further investigated the role of mTOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
(86 reference statements)
1
16
0
Order By: Relevance
“…Furthermore, Zhu et al showed that mTOR inhibition suppress eosinophil differentiation in allergic airway inflammation [64], Shin and coll. that reduces eosinophil infiltration and Th2 immune response [65] and Fang et al that IgE induced airway smooth muscle cell (ASMC) remodeling was significantly reduced by inhibition of mTOR [66] while Rakhmanova et al suggested as a therapeutic strategy for mast cell-related diseases the hyperactivation of mTORC1 [67].…”
Section: Asthma and Rhinitismentioning
confidence: 99%
“…Furthermore, Zhu et al showed that mTOR inhibition suppress eosinophil differentiation in allergic airway inflammation [64], Shin and coll. that reduces eosinophil infiltration and Th2 immune response [65] and Fang et al that IgE induced airway smooth muscle cell (ASMC) remodeling was significantly reduced by inhibition of mTOR [66] while Rakhmanova et al suggested as a therapeutic strategy for mast cell-related diseases the hyperactivation of mTORC1 [67].…”
Section: Asthma and Rhinitismentioning
confidence: 99%
“…Eosinophil extracellular trap formation has also been found to be correlated with autophagy levels (21,22), but interestingly Atg5 knockout was not necessary for their formation (82). Autophagy may have a role in the differentiation of eosinophils, however the only study of it has been through regulators, such as mTOR which regulates it indirectly (86,87). Like neutrophils, eosinophils have also been observed to go through an autophagy-mediated caspase-independent cell death in inflammatory conditions (88).…”
Section: Role Of Autophagy In Myeloid Cells Granulocytesmentioning
confidence: 99%
“…This increase was partially related to an up-regulation of GATA1 with mTOR inhibition. Interestingly, mTOR deletion in myeloid cells promotes eosinophil development but disrupts neutrophil development [ 72 ].…”
Section: Role Of Mtor Signalling In Haemopoiesismentioning
confidence: 99%